2022
DOI: 10.1177/07334648211067710
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors Among Older Adults: A Scoping Review

Abstract: Although older adults may experience health challenges requiring increased care, they often do not ask for help. This scoping review explores the factors associated with the help-seeking behaviors of older adults, and briefly discusses how minority ethnic populations can face additional challenges in help-seeking, due to factors such as language barriers and differing health beliefs. Guided by Arksey and O’Malley’s scoping review framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 82 publications
5
28
0
Order By: Relevance
“…This tendency contributed to improving and maintaining mental health, regardless of gender. This finding is consistent with previous studies 3–5 and suggests that people tend to seek help from others when they encounter problems they cannot resolve on their own.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This tendency contributed to improving and maintaining mental health, regardless of gender. This finding is consistent with previous studies 3–5 and suggests that people tend to seek help from others when they encounter problems they cannot resolve on their own.…”
Section: Discussionsupporting
confidence: 93%
“…[1][2][3] Previous studies have reported correlations between whether people decide to seek help and the problem severity. [3][4][5] For example, Phillips and Murrell (1994) reported that the middle-aged and older adults in their study who sought help experienced more stressful events than those who did not seek help. 5 This finding suggests that middle-aged and older adults facing more severe problems are more likely to engage in help-seeking behaviours compared to those who have experienced less severe ones.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the gender ratio of self‐harm rates usually seen in younger age groups was not observed, with the rate higher in men aged 75 years and over than in women of the same age which aligns with previous findings 6,11 . This gender reversal and the increase in rates in 60–74 years olds might be explained by men, including those in older age groups, having lower levels of help‐seeking behaviour and consequently being less likely to access health services than do women 17,34 . This is supported by our findings that men over 60 years were less likely to have been receiving psychiatric treatment at the time of self‐harm or have received such treatment in the past, despite a similar proportion of men and women having a history of self‐harm over the 12 months preceding their self‐harm presentation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have focused on the possible reasons for underutilization of HCBS in older adults. Although older people are the main consumers of healthcare services, stereotypes, prejudice, discrimination, and structural obstacles such as inconvenient transportation, shortage of geriatric specialists, and the spread of digital healthcare make it difficult for older people to access relevant resources [19,20]. Our research team conducted a qualitative study to reconstructed the paths and obstacles encountered by older adults in seeking community care services, and found multiple barriers, which were lack of community care information, limited mobility, complex process of achieving care, and incomprehension of needs expression, deterred the access of care resources for older adults effectively [21].…”
Section: Introductionmentioning
confidence: 99%